Rituximab treatment in pediatric patients with steroid-dependent nephrotic syndrome: A tertiary hospital - Beatriz Guzmán Morais; Flor Ángel Ordóñez Álvarez; Fernando Santos Rodríguez; Silvia Martín Ramos; Gema Fernández Novo (Elsevier, 2022)
Background: Corticosteroids have had a central role in the treatment of nephrotic syndrome. The management of these patients who become dependent to steroids is complex, involving different immunosuppressive drugs patterns. The monoclonal antibody anti CD20, Rituximab, is likely to have beneficial effects in cases of steroid-dependent nephrotic syndrome patients with no easy resolution, even when we cannot make a statement about the specific role in the impact. We bring our personal experience in pediatric patients treated with this medication during the last years, to provide a thorough overview and useful information about the role of Rituximab in this pathology. Methods: Retrospective study in patients with steroid-dependent idiopathic nephrotic syndrome controlled in the division of Pediatric Nephrology of a Spanish tertiary hospital in those patients who had received at least one treatment cycle of Rituximab, at any moment along the evolution of the disease. Results: The study involved 8 patients. All of them previously received immunosuppressive therapy. The Rituximab were administered as an intravenous infusion, in a dose of 375 mg/m2, and all doses were administered in a period during which the disease was in remission. The depletion of lymphocytes B (CD19, 0%) were confirmed after the first dose of Rituximab except for one, with a lymphocyte count of 1%. The period of depletion lasts 10,3 months (median; range 6,5-16 months), and only one of the patients registered a relapse of the disease in this period. A reduction of relapses suffered by patients has been shown after the treatment began (3,6 relapses/year in the previous year to the start of the treatment versus 0,1 relapses/year during the first year post-rituximab). The relapse-free survival in the first year reached 83,3% in patients who suffered more than one relapse (75% of patients), and without a relapse after the treatment began in 2 cases. One or more drugs could be removed in 87,5% of patients after the first cycle of rituximab. After the rituximab treatment, we reached a 96,5% decrease in the corticosteroids doses administered (28,5 mg/m2/day during the 3 months pre-treatment versus 1 mg/m2/day in the last 3 months of patient monitoring). Not a significant observed adverse effect attributed to the drug after the post-rituximab monitoring period (median 46,5 months, range 5-97 months). Conclusion: The favorable results reported after rituximab treatment in our patients seems to confirm the effectiveness of this drug in the steroid-dependent nephrotic syndrome, making that therapeutic option into consideration and legitimating the use of the drug in complex cases involving pediatric patients. Even so, it seems recommendable to design pertinent studies to clarify, among others, the optimum regimen of the treatment (dose, interval and cycles), clinical repercussion and potential adverse effects in long terms. Resumen: Introducción: La corticoterapia continúa siendo la piedra angular en el tratamiento del síndrome nefrótico. El manejo de los pacientes que desarrollan dependencia a esteroides es complejo, implicando distintas pautas de fármacos inmunosupresores. El rituximab, anticuerpo monoclonal anti-CD20, parece tener efectos beneficiosos en pacientes con síndrome nefrótico córtico-dependiente de difícil manejo clínico, si bien aún no está bien definido su papel en esta entidad. Con el fin de aportar información útil sobre el papel del rituximab en esta patología, presentamos nuestra experiencia personal en pacientes pediátricos tratados con este fármaco en los últimos años. Materiales y métodos: Estudio retrospectivo en pacientes con síndrome nefrótico idiopático cortico-dependiente controlados en la Sección de Nefrología Pediátrica de un hospital terciario español y que habían recibido, al menos, un ciclo de tratamiento con rituximab durante cualquier momento de la evolución de la enfermedad. Resultados: Se incluyeron en el estudio 8 pacientes. Todos habían recibido terapia inmunosupresora previamente. El rituximab se administró por vía intravenosa a una dosis de 375 mg/m2, y todas las dosis se administraron en situación de remisión de la enfermedad. Se confirmó la depleción completa de linfocitos B (CD19, 0%) tras la primera dosis de rituximab en todos excepto en uno, en el que el recuento fue del 1%. El período de depleción fue de 10,3 meses (mediana; rango 6,5-16 meses), y solamente en uno de los pacientes se registró una recaída de la enfermedad durante este período. Tras el inicio del tratamiento, se observó una reducción del número de recaídas (3,6 recaídas/año en el año previo al inicio del tratamiento versus 0,1 recaídas/año durante el primer año post-rituximab). La supervivencia libre de recaída en el primer año fue del 83,3% en los pacientes con más de una recaída (75% de los pacientes), sin existir recaídas tras el inicio del tratamiento en 2 pacientes. En un 87,5% de los pacientes se pudieron retirar uno o más fármacos tras el primer ciclo de rituximab. Tras el tratamiento con rituximab, se consiguió una reducción del 96,5% de las dosis de corticoides administrados (28,5 mg/m2/día en los 3 meses pre-tratamiento versus 1 mg/m2/día en los 3 últimos meses de seguimiento en los pacientes tratados). Tras el periodo de seguimiento post-rituximab (mediana 46,5 meses, rango 5-97 meses), no se observaron efectos adversos significativos atribuibles al fármaco. Conclusiones: Los resultados favorables reportados tras el tratamiento con rituximab en nuestros pacientes parecen confirmar la eficacia del fármaco en el síndrome nefrótico córtico-dependiente y lo hacen considerar como una opción terapéutica válida en casos de difícil manejo clínico en la edad pediátrica. Aun así, parece recomendable diseñar estudios apropiados que traten de aclarar, entre otros, el régimen óptimo de tratamiento (dosis, intervalo y número de ciclos), repercusión clínica y potenciales efectos adversos a largo plazo.